Correlation Between Soil-Transmitted Helminth (STH) Infection and Eosinophil Score on Residents Around Landfill of Mojosongo Village, Jebres Sub-District, Surakarta City - Rochmadina Suci Bestari; Supargiyono Supargiyono; Sumarni Sumarni; Suyoko Suyoko (Pusat Kedokteran Tropis, 2017)
Introduction: Soil-Transmitted Helminth (STH) infected more than one million people all over the world. In Indonesia, the prevalence of STH infection is still high in a few places, some of them are 40-60 % of all ages, with different species of helminth and intensity. Citizens around landfills usually has unhealthy sanitary and life style. Some data indicated that they often suffer alergic symptoms, like itchy on the skin and chronic coughing which could be due to STH infection.Objectives: This study was held to know the relationship between STH infection and eosinophil score at citizens around landfills of Kelurahan Mojosongo Kecamatan Jebres Kota Surakarta, Central Java, Indonesia.Methods: Stool and blood sample from 96 citizens of study site who agreed to participate (by informed consent) were collected. Kato-Katz method was used to determine the helminths infection intensity. Eosinophil count was done on thin blood smear stained with Giemsa to identify the percentage of eosinophil among other cells on the blood smear subjects. .Results: Prevalence of STH infection was 7,29% (7/96) with egg density of 61 Eggs Per Gram Feses (EPGF). Single type of helminth infection occured among the participants and there was no co-infection. Hookworm infection was 6,25% (6/96) and Trichuris trichiura infection was 1,04% (1/96). There was no Ascaris lumbricoides infection. All of them were fall into catagory of light infection. The prevalence of eosinophilia was 27,8% (26/96) with 2,63% mean osinophil percentage. There was a very weak association between STH infection intensity and eosinophil score (r=0,190; p=0,032).Conclusion: The prevalence of STH infection of the population around landfills of Mojosongo, Surakarta was 7,29% and predominated by Hookworm. There was a very weak association between STH infection intensity and eosinophil score (r=0,190; p=0,032). Keywords: STH infection, STH infection intensity, eosinophil score, Kato-Katz, eosinophiliaINTISARIPendahuluan: Soil-Transmitted Helminth (STH) menginfeksi lebih dari satu milyar orang di seluruh dunia. Di Indonesia, prevalensi STH di beberapa tempat juga masih tinggi, ada diantaranya dengan prevalensi 40-60 % pada semua umur, dengan jenis cacing dan intensitas yang berbeda-beda. Masyarakat yang tinggal di sekitar Tempat Pembuangan sampah Akhir (TPA) biasanya sanitasi lingkungan dan kebiasaan hidupnya tidak sehat. Beberapa data menunjukkan bahwa mereka biasanya mengeluhkan adanya gejala alergi seperti gatal-gatal pada kulit dan batuk kronis yang sangat mungkin disebabkan olef infeksi STH.Tujuan: Penelitian ini dilaksanakan untuk mengetahui hubungan infeksi STH dengan angka eosinofil pada masyarakat di sekitar TPA Kelurahan Mojosongo Kecamatan Jebres Kota Surakarta, Jawa Tengah, Indonesia.Metode : Sampel tinja dan darah dikoleksi dari 96 warga yang bersedia berpartisipasi (dengan informed consent). Metode Kato-Katz digunakan untuk mengetahui adanya infeksi STH dan mengetahui intensitas infeksinya. Hitung eosinofil dilakukan pada sediaan apus darah tipis yang dipulas dengan Giemsa untuk mengetahui persentase eosinofil pada penderita.Hasil: Prevalensi infeksi STH secara keseluruhan sebesar 7,29% (7/96) dengan rata-rata jumlah telur 61 telur per gram feses. Semua menderita infeksi tunggal dan tidak ada yang infeksi campuran. Infeksi hookworm sebesar 6,25% (6/96) dan infeksi Trichuris trichiura sebesar 1,04% (1/96). Tidak ditemukan infeksi Ascaris lumbricoides. Semuanya menderita infeksi ringan. Prevalensi eosinofilia adalah 27,8% (26/96) dengan rata-rata persentase eosinofil 2,63%. Terdapat hubungan yang signifikan antara intensitas infeksi STH dengan angka eosinofil, dengan kekuatan sangat lemah (r=0,190; p=0,032).Simpulan: Terdapat hubungan yang signifikan antara intensitas infeksi STH dengan angka eosinofil, dengan kekuatan sangat lemah (r=0,190; p=0,032). Kata kunci : infeksi STH, intensitas infeksi STH, angka eosinofil, Kato-Katz, eosinofilia